Мониторинг стабильности технологического процесса изготовления электроизоляционных систем тяговых электрических машин - Беспрозванных, Анна Викторовна; Рогинский, Александр Владимирович (НТУ "ХПИ", 2017)
Показано, что сопротивление изоляции может служить информативным параметром стабильности технологического процесса изготовления электроизоляционных систем тяговых электрических машин. Установлено, что сопротивление изоляции находится в пределах ±3σ относительно среднего значения каждой выборки трех вариантов исполнения электроизоляционной системы. Представлены контрольные карты индивидуальных значений и кумулятивных сумм сопротивления изоляции магнитной системы тяговых электродвигателей постоянного тока.

Introduction. Electrical insulation systems make up about 0.03 % of the traction electric machines (TEM) mass, but they are of exceptional importance and affect the design capabilities and manufacturing techniques of electric machines, ultimately - on their specific weight and overall dimensions, on the reliability and durability of the TEM. Purpose. The monitoring of the stability of the manufacturing process of electrical insulating systems of the TEM based on the insulation resistance measurements. Methodology. The analysis of the manufacturing process is carried out for three versions of the case of insulation of the magnetic system of the DC traction electric motor. Practical value. Construction and analysis of special graphs (charts) of individual values and cumulative sums of insulation resistance, sliding range MR allow to find out whether the technological process of manufacturing electric insulating systems of traction electric machines is in a statistically controllable state.
The stability monitoring of the manufacturing process of electrical insulating systems of traction electric machines
Keywords: машина электрическая; машина тяговая; система электроизоляционная; сопротивление изоляции; карта контрольная; сумма кумулятивная; процесс технологический; traction electrical machines; electrical insulation systems; insulation resistance; cumulative sum; control chart; manufacturing process